Demographic, Environmental and Clinical Correlates of Intestinal Parasitic Infections Among Patients Attending Primary Healthcare Centers in Demsa Local Government Area of Adamawa State - K, Mijah A.; T, Jerry J.; A, Solomon; H, Abdulrasheed M.; J., Agere H. I. (Darul Yasin Al Sys, 2026)
Intestinal parasitic infections (IPIs) remain a major public health problem in Nigeria, particularly in rural communities where sanitation and access to clean water are limited. This study investigated the prevalence and correlates of IPIs among patients attending primary healthcare centers (PHCCs) in Demsa Local Government Area (LGA), Adamawa State. A descriptive cross-sectional design was employed, and stool and blood samples were collected from 398 participants using systematic random sampling. Parasitological analysis was conducted using the formol-ether concentration technique, and data were analyzed with descriptive statistics and chi-square tests at a significance level of p < 0.05. The overall prevalence of IPIs was 37.4%, with Ascaris lumbricoides (14.9%) and hookworm (11.1%) being the most common parasites. Infection prevalence was significantly associated with age (p = 0.04), occupation (p = 0.02), open defecation (p = 0.001), living near stagnant water (p = 0.005), and lack of regular deworming (p < 0.001), with children aged 11–15 years and individuals using river water sources being particularly vulnerable. Attendance at health education programs was associated with lower infection rates (p = 0.006). The findings emphasize the persistence of IPIs in Demsa LGA, driven by poor sanitation, unsafe water use, and inadequate hygiene practices, and support the need for strengthened community health education, regular deworming, improved sanitation infrastructure, and safe water access to reduce the disease burden and enhance rural health outcomes.